An inductive content analysis of formative feedback given by lived experience assessors in pre-registration mental health nurse education. Issue 1 (10th January 2020) - Stacey, Gemma; Pearson, Mark
Abstract : Purpose: In the assessment of student nurses, there is limited research exploring why the contributions of people with lived experience (LE) have an impact on learning. The purpose of this paper is to compare the nature of feedback provided to students by people who have both worked in and used mental health services. Design/methodology/approach: To explore the nature of qualitative student feedback generated from an assessment involving people who have experience of using and working in mental health services. Therefore, an inductive content analysis conducted on the formative written feedback provided to students following a simulated assessment. Findings: The results demonstrate significant similarities in the feedback provided by those with LE of using and working within mental health services, suggesting a shared conceptualisation of professionalism. Research limitations/implications: The research indicates the potential socialisation of professionals and service users to not only the assessment process but also the professional expectations of mental health nurses. These findings resonate with Barker et al. 's (1999) description of the "pseudo ordinary me" and emphasise the principles and importance of person-centred care. Originality/value: The paper highlights that assessment approaches which incorporate feedback from people with LE offer a vehicle to demonstrate and explore how attributes, subjectively associated with professionalism, can be recognised and developed by student mental health nurses.